Hubungan Antara Sikat Gigi Menggunakan Pasta Gigi dan Tanpa Pasta Gigi Terhadap Score Plak Gigi Pada Siswa Sekolah Dasar - Almujadi, Almujadi; Eni Purwati, Dwi (Journal of Oral Health Care, 2018)
Cleaned toothbrushing is an activity to clean all the surface of teeth by using tooth brush and tooth paste. This study purposes to know the relationship between tooth brushing with and without toothpaste and plaques score in elementary school students. This study used quasi experiment study design. This study population and subject were all of students in class IV and V SD Negeri Kandangan I and SD Negeri Kandangan II. Seventy students were divided into intervention and control group, with each group contained 35 students. Plaque data was evaluated by using plaque coloring material disclosing solution which was dropped on the tip of the tongue then spread on teeth surfaces. Plaque score was measured by Personal Hygiene Performan-Modified (PHP-M) technique using all plaque scores on the index teeth. Data analysis were performed by independent t-test, with normality and homogeneity test were performed before it. This study showed that there was significant difference in tooth plaque scores decline between experimental group and control group. Experimental group declined as much or 22,94, wherias control group declined at much as 11,00. This study concluded Tooth brushing with toothpaste could reduce plaque score in elementary school students compared to tooth brushing without toothpaste.